Modeling the costs of project transportation maintenance - Rusanova, Svitlana (Technology audit and production reserves, 2020)
This study investigates variants in transportation maintenance of projects. The study subject is the mathematical notation of the dependence of costs incurred during the transportation maintenance of a project on the characteristics of maintenance options. Most projects involve a transportation component, which relates to the need to deliver raw materials, materials, equipment, manpower to the location of the product project (for example, construction projects, infrastructure projects). This study aims to identify variants in the transportation maintenance of projects, to establish mathematical dependences of transportation costs depending on the characteristics of vehicles and the conditions for their use in projects. The characteristics of the vehicles and the conditions of their operation in the projects form the essence of a specific variant of the transportation maintenance of a project. Each alternative transportation maintenance option affects the project, first of all, at the cost level. Therefore, the optimal transportation maintenance variant for a project should be selected considering the impact of options on project costs. In this study, the basis for modeling the cost of a project’s transportation maintenance is the project’s network schedule and an analysis of its activities in terms of the need for transportation maintenance. Mathematical expressions for the volume of transportation operations and the required number of vehicles of different types have been consistently derived. Cost dependences for three variants of vehicle utilization (rent, service, acquisition) have been derived, based on vehicle characteristics, for three levels of project consideration: certain operations, a certain time span, the project in general. The resulting formalization of transportation maintenance costs makes it possible to vary the characteristics of vehicles and the conditions for their use in a project during the decision-making phase of choosing the transportation maintenance option for a project, or their combination. The reported results underlie further development of the model for optimizing parameters and choosing the transportation maintenance variant of projects